2020
DOI: 10.3389/fonc.2020.00208
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Evaluation and Clinical Prognostic Values of m6A RNA Methylation Regulators in Glioblastoma

Abstract: N6-methyladenosine (m6A) RNA methylation, the most common form of mRNA modification and regulated by the m6A RNA methylation regulators ("writers," "erasers," and "readers"), has been reported to be associated with the progression of the malignant tumor. However, its role in glioblastoma (GBM) has been poorly known. This study aimed to identify the expression, potential functions, and prognostic values of m6A RNA methylation regulators in GBM. Here, we revealed that the 13 central m6A RNA methylation regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 81 publications
(81 reference statements)
0
39
0
Order By: Relevance
“…Previous studies have reported the bioinformatics analysis of total 13 m 6 A-related genes in gastric cancer ( 17 ), bladder cancer ( 18 ), and other cancers ( 19 , 20 ). In our study, a total of 19 m 6 A RNA methylation regulators were included for systematically analysis based on the recent the m 6 A review ( 9 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported the bioinformatics analysis of total 13 m 6 A-related genes in gastric cancer ( 17 ), bladder cancer ( 18 ), and other cancers ( 19 , 20 ). In our study, a total of 19 m 6 A RNA methylation regulators were included for systematically analysis based on the recent the m 6 A review ( 9 ).…”
Section: Methodsmentioning
confidence: 99%
“…MTT was applied to test the viability of GSCs. It is worth noting that YTHDF2, as a reader of RNA m6A methylation, has been validated to be related to TMZ resistance in GSCs (Du et al, 2020). We found that TMZ and shYTHDF2 could synergistically inhibit the viability of GSCs (Figure 8H).…”
Section: Knockdown Of the Hub Proteinsmentioning
confidence: 68%
“…Certain types of RNA modifications in eukaryotic mRNA, such as 5‐methylcytosine (m5C), N1‐methyladenosine (m1A) and N6‐methyladenosine (m6A), have widely discovered, 4 among which m6A RNA methylation was first discovered in the 1970s 5 . The m6A RNA methylation, the most common form of dynamic and reversible mRNA modification, is regulated by m6A RNA methylation regulators, containing methyltransferases (‘writers’) that install m6A mark, demethylases (‘erasers’) that reverse m6A mark, and m6A binding proteins (‘readers’) that decode m6A modification to mediate the fate of modified transcripts 6–8 . Currently, at least ten proteins have been found in the m6A ‘writers’ complex, containing WT1‐associated protein (WTAP), methyltransferase like 3/4/14 (METTL3/4/14), Cbl Proto‐Oncogene Like 1 (CBLL1), RNA‐binding motif protein15/15B (RBM15/15B), Vir like m6A methyltransferase associated VIRMA (VIRMA/KIAA1429), Zinc Finger Protein 217 (ZNF217) and zinc finger CCCH domain‐containing protein 13 (ZC3H13) 3,4,6,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Twelve proteins have been identified in the m6A 'readers', including YT521-B homology (YTH) domain-containing proteins (YTHDC1/2), eukaryotic translation initiation factor 3 subunit A/B (EIF3A/B), YTH N6-methyladenosine RNA-binding proteins (YTHDF1/2/3), insulin like growth factor 2 mRNA binding protein families (IGF2BP1/2/3) and heterogeneous nuclear ribonucleoprotein (HNRNP) protein families (HNRNPA2B1 and HNRNPC). 3,4,6,8,9 The m6A RNA methylation modulated by these regulators has been found to influence mRNA at different levels, containing structure, maturation, splicing, nuclear export, translation, localization, stability and decay, 3,4,[6][7][8][9] playing important roles in diverse physiological processes, including development, fertility, stemness, meiosis, carcinogenesis, circadian cycle, cell fate decision, cell differentiation, cell cycle regulation and circadian rhythm maintenance and human diseases. 6,8,10 Particularly, an increasing number of in vivo and in vitro experiments and bioinformatic researches showed that m6A RNA methylation regulators contribute to the occurrence, development and clinical prognosis of multiple various cancers, 4,[6][7][8][9][11][12][13][14] while the role of m6A RNA methylation regulators in COPD and their association with COPD genes are never reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation